Mechanical Properties and Wellbore Stability Analysis of Beipiao Oil Shale - Li, Zigui; Bo, Kun (Journal of Progress in Civil Engineering, 2026)
This study analyzes the wellbore stability of Beipiao oil shale in Liaoning Province. XRD analysis and triaxial compression tests, conducted at bedding inclination intervals of 30° (0°, 30°, 60°, and 90°), characterize the samples as hard-brittle shale with significant mechanical anisotropy. Specifically, the cohesion and internal friction angle of the rock matrix are 17.15 MPa and 36.21°, respectively, while those of the bedding weak planes are significantly lower at 8.95 MPa and 25.85°. By coupling a transversely isotropic model with Jaeger’s criterion, the collapse pressure equivalent density was calculated under various in-situ stress regimes. The results indicate that the optimal drilling trajectory varies with the stress regime: under strike-slip and reverse faulting conditions, the optimal trajectory aligns with the maximum horizontal in-situ stress (σH), whereas under normal faulting conditions, it aligns with the minimum horizontal in-situ stress (σh). These findings provide a theoretical basis for trajectory optimization in hard-brittle laminated formations.